Synchrotron FTIR spectromicroscopy as a tool for studying populations and individual living cells of green algae. Issue 24 (14th October 2020) - Goff, Kira L.; Ellis, Thomas H.; Wilson, Kenneth E.
Abstract : Fourier transform infrared (FTIR) spectromicroscopy was used to study variations in individual living cells of the green algal genus Chlamydomonas and to distinguuish between three closely-related species. Abstract : Fourier transform infrared (FTIR) spectromicroscopy was used to study individual living cells of three closely-related species of the green algal genus Chlamydomonas . Three types of spectral variation were observed between individual cells within a single culture, as well as between different cultures: variation around a mean, individual outliers, and the presence of subpopulations. By understanding and controlling this variation, we were able to spectroscopically differentiate between the three closely-related species. Spectral differences were confirmed using principal component analysis, leading to an understanding of the biochemical differences between species. This work highlights the additional information obtained by studying individual cells, and has implications for more traditional bulk measurements.